PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS X DI SMA NEGERI 1 PUDING BESAR (QUASI EKSPERIMEN) - Kolbia, Suci; Zayadi, Zayadi; Wahyuni, Vera (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
The background of this research is the subject of Islamic Religious Education and Character Education which is considered boring and monotonous because it is often taught with less varied learning methods and models so that students have a passive nature in learning which results in a lack of student learning outcomes, especially in terms of critical thinking. . This research aims to determine the effect of implementing a type of cooperative learning model jigsaw on critical thinking skills in the subjects of Islamic Religious Education and Character in class X at SMA Negeri 1 Puding Besar. This type of research is a quantitative experiment with Quasi Experimental Design. The population used was all class X, totaling four classes, while the samples were taken using techniques simple random sampling is class X-1 as the experimental class and class X-3 as the control class. The data collection technique used in this research is the test (pre-test and post-test) which each amount to 10 HOTS shaped questions essay. The hypothesis test used is the t-test in the form of Independent Sample T-Test. The results of this research are hypothesis testing with Independent Sample T-Test Using a significance level of 5% (α = 0.05), the Sig value is known. (2-tailed) is 0.000. At the decision making criteria 0.000 < 0.05, then H0 rejected and H1 accepted. So there is a significant influence of the type of cooperative learning model jigsaw on critical thinking skills in the subjects of Islamic Religious Education and Character in class X at SMA Negeri 1 Puding Besar.